Strategi Rehabilitas Lahan Kritis di Hutan Lindung Bukit Suligi Kabupaten Rokan Hulu - Rosef Putra; Wawan Wawan; Nofrizal Nofrizal (Pelantar Press, 2025)
An evaluation of land cover change and erosion hazard was conducted to develop effective rehabilitation strategies in the Bukit Suligi area, Riau. Satellite imagery from 2014, 2019, and 2023, analyzed using land cover classification and NDVI, showed an increase in moderate vegetation cover from 58.77% to 82.65%, with 2.88 hectares of open land. Erosion estimates using the Universal Soil Loss Equation (USLE) indicated the highest potential erosion on cropland/open land (20.4 tons/ha/year) and the lowest on protected forest (4.7 tons/ha/year). The Erosion Hazard Index (EHI), calculated using actual erosion and a Tolerable Soil Loss (TSL) value of 11.2 tons/ha/year, identified 1,200 hectares as low hazard (EHI 0.05) and 283 hectares as high hazard (EHI ≥ 0.15). Rehabilitation strategies were prioritized using the Analytical Hierarchy Process (AHP), incorporating ecological, social, institutional, and technological criteria. Soil and water conservation emerged as the top priority (weight 0.320), followed by community participation, institutional support, and technology. Recommended actions include terracing, check dams, reforestation with native species, agroforestry, economic incentives, and ongoing monitoring. These results support sustainable rehabilitation planning in similar landscapes